The optimization of iloprost inhalation under moderate flow of oxygen therapy in severe pulmonary arterial hypertension - Kazuhiko Nakayama; Noriaki Emoto; Naoki Tamada; Mitsumasa Okano; Yuto Shinkura; Kenichi Yanaka; Hiroyuki Onishi; Mana Hiraishi; Shinichiro Yamada; Hidekazu Tanaka; Toshiro Shinke; Ken-ichi Hirata (Pulmonary Circulation, 2018)
Inhaled iloprost efficiently improves pulmonary hemodynamics, exercise capacity, and quality of life in patients with pulmonary arterial hypertension (PAH). However, the process of inhalation is laborious for patients suffering from resting dyspnea. We describe a 75-year-old man with idiopathic PAH and a low gas transfer. Investigations excluded significant parenchymal lung disease and airflow obstruction (presuming FEV1/FVC ration > 70%). The patient struggled to complete iloprost inhalation due to severe dyspnea and hypoxemia. As such, we optimized the methods of oxygen supply from the nasal cannula to the trans-inhalator during the inhalation. We successfully shortened the inhalation duration that effectively reduced the laborious efforts required of patients. We also recorded pulmonary hemodynamics during inhalation of nebulized iloprost. This revealed significant hemodynamic improvement immediately following inhalation but hemodynamics returned to baseline within 2 hours. We hope that this optimization will enable patients with severe PAH to undergo iloprost inhalation.